Dari Wombu ke Woda: Transformasi Nilai budaya dalam siklus kehudupan masyarakat nagekeo di era modern - Mere, Klemens (Community Engagement and Emergence Journal (CEEJ), 2025)
This study explores the transformation of cultural values within the life-cycle traditions of the Nagekeo community in Flores, focusing on how modernization and religion influence long-standing rituals from wombu (birth) to woda (death). The research employs a qualitative literature review approach based on studies from 2020–2025 that examine cultural continuity, adaptation, and intergenerational transmission in local communities. Findings reveal that traditional practices in Nagekeo are undergoing reinterpretation: symbolic rituals once centered on ancestral spirituality are increasingly blended with religious teachings and modern values. While modernization introduces efficiency and new forms of expression, it also challenges communal participation and spiritual depth. Nevertheless, the community demonstrates adaptive resilience—preserving core ethical and social meanings while reshaping ceremonies to align with contemporary life. The transformation from wombu to woda thus represents not a cultural decline, but an ongoing negotiation between heritage, faith, and modern identity.